Oral manifestations of Alagille-2 syndrome: a rare case report - Sharma, Arun Dev; Parihar, Ajay; Reddy, Prashanthi; Mandlik, Rashi (International Journal of Research in Medical Sciences, 2023)
Alagille-2 syndrome (AGLS-2) is a rare autosomal dominant illness that affects the Notch signalling pathway, with few studies reported in the literature related to dental science. It is recognized clinically, with anomalies of the liver, skeleton, kidneys, eyes, and face manifesting. The JAG1 gene accounts for about 97 percent of instances of Alagille syndrome variation, whereas mutations in NOTCH2 account for only 1 percent. When serum bilirubin levels in children are higher than 30 mg/dl, bilirubin builds up in dental tissue and results in varied greenish-brown dyschromia of the teeth. We discussed the dental findings of a patient diagnosed with NOTCH-2 who sought out dental treatment at the government college of dentistry in Indore, MP (India), complaining of pain and a stain in his teeth with typical features of facial dysmorphism.